Evaluation of dynamics of economic development in Polish and Lithuanian regions - Lisiński, Marek; Augustinaitis, Arūnas; Nazarko, Lukasz; Ratajczak, Sabina (Journal of Business Economics and Management, 2020)
Regional policy of the countries – reducing disparities between economic development of the regions – has been, is and will continue to be the focus of policy makers’ attention, therefore it is important to assess regional conditions qualitatively and to spot the differences in the change of these condition. This would be the basis for developing targeted strategies for further regional development. The process of regional economic development may be assessed quantitatively and qualitatively. The integrated mean of the statistical indicators reflects the dynamics of development. The paper’s objective is to develop an aggregate indicator of development dynamics and to quantify the dynamics of the economic development of the Polish and Lithuanian regions. The employed methodological approach is based on the authors’ definition of the mean of regional economic development equilibrium. The analysis of the statistical characteristics of the indicators of three regions of Poland and Lithuania has shown that the dynamics of economic development in the regions of both countries is similar. On the other hand, Poland is characterized by a more intensive development, while the development of Lithuanian regions is more levelled.